TEACHERS’ PERCEPTION OF PEERAGOGY IN ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Eska Perdana Prasetya; Nuraeni Nuraeni; M Shabir (STKIP Persada Khatulistiwa Sintang, 2022)
This covid 19 pandemic has made all life arrangements drastically change, not to mention the world of education, to avoid the increasingly widespread spread of the corona virus, it was changed from face-to-face learning in class to face-to-face or online learning using the zoom or goggle meet application. This research is a digital ethnography research, method or strategy in research to uncover a particular case. The research is oriented to the perception of teachers in learning using peeragogy strategies in online learning during the covid 19 pandemic. Perception is the experience of objects, events, or relationships obtained by inferring information and interpreting messages. Some results found that peeragogy can be applied in online learning because it makes students active, can be very good for honing children's activities in online learning, used to make students bring out latent abilities, and in groups can create a sense of responsibility. However, in online learning, various shortcomings can also be found, such as network problems, students who do not have gadgets and quotas.